PENGENALAN KETERAMPILAN MEMBACA ANAK USIA DINI DI TK IT QUANTUM MULIA KROYA - Wahyu; Anjarwati, Risna; Nurbaiti, Amalia (Universitas Negeri Jakarta, 2021)
The introduction of early childhood reading skills at the Quantum Mulia Kroya Islamic Kindergarten is carried out through learning and playing activities which are based on three important activities: First, planning activities that organize the goals, time, and materials that have been determined for learning and playing activities, and teachers who already understand the important tasks in teaching. Second, learning and playing activities that organize bound books as a medium and learning resource; habituation as the basis for learning activities; and the preparation of a reading corner to support learning in one learning activity. Third, assessment activities are carried out by organizing the Children's Achievement Book and direct observation which functions to assess children's objective results in learning objectively and comprehensively. Through these three learning and playing activities, early childhood at TK IT Quantum Mulia Kroya can develop their reading skills recognition well.